KONTEKSTASI PILPRES 2014 & 2019 TERHADAP REMAJA MILENIAL SEBAGAI SUMBER INSPIRASI PENCIPTAAN KARYA SENI LUKIS - Gatrin Rukmanandi; Amir Gozali (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
Creation of a painting with a background of anxiety as well as the experience that has been generated from the 2014 & 2019 presidential election at that time. The presidential elections in 2014 and 2019 at that time made a lot of people especially teenagers in the millennial generation to receive the negative impacts they received directly and indirectly. These incidents also shape the attitudes of the millennial generation to face the turmoil of this presidential election. The purpose of creating this artwork is to explain the concept, process and visual description of the work whose source of inspiration comes from the context of the 2014 & 2019 presidential elections for millennial youth. The painting style used is the Pop Surrealism style. The creation of works refers to the three stages of creation put forward by Herman Von Helmholtz which describes the stages in the creation process, including: Saturation (Data Collection), Incubation (Precipitation), Illumination (Embodiment of Work). The creation of this painting work provide more insight into the tools, materials, techniques of working on a work. The results obtained from the creation of the work are paintings inspired by the context of the 2014 & 2019 presidential elections for millennial youth. Another result is empirical experience and the deepening of concepts in the creation of painting works with the inspiration for the context of the 2014 & 2019 presidential elections for millennial youth.